Is Ultrasonography Useful in the Diagnosis of Nasolabial Cyst? - Ahmet H. Acar; Ümit Yolcu; Fatih Asutay (Hindawi Limited, 2014)
Nasolabial cysts are nonodontogenic cysts that occur beneath the ala nasi. Its pathogenesis is uncertain. Because the nasolabial cyst is a soft tissue lesion, plain radiographs are useless. CT and MRI should be evaluated. In this report, a nasolabial cyst is described including its features on ultrasonography (USG) and CT exams.